2020
DOI: 10.1101/2020.01.09.900209
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ADAM17-triggered TNF signalling protects the ageing Drosophila retina from lipid droplet mediated degeneration

Abstract: Animals have evolved multiple mechanisms to protect themselves from the cumulative effects of age-related cellular damage. Here we reveal an unexpected link between the TNF (tumour necrosis factor) inflammatory pathway, triggered by the metalloprotease ADAM17/TACE, and a lipid droplet (LD)-mediated mechanism of protecting retinal cells from age related degeneration. Loss of ADAM17, TNF and the TNF receptor Grindelwald in pigmented glial cells of the Drosophila retina leads to age related degeneration of both g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 77 publications
1
8
0
Order By: Relevance
“…Similar reasoning suggests a reinterpretation of two previous studies in the adult Drosophila retina, which reported that glial lipid droplets induced either by mitochondrial defects or by loss of ADAM17 metalloprotease act to promote neurodegeneration [57,58]. This conclusion was based on evidence that decreasing lipid droplets via the overexpression of Bmm/ATGL leads to less neurodegeneration.…”
Section: A General Strategy For Distinguishing Between Different Lipisupporting
confidence: 70%
“…Similar reasoning suggests a reinterpretation of two previous studies in the adult Drosophila retina, which reported that glial lipid droplets induced either by mitochondrial defects or by loss of ADAM17 metalloprotease act to promote neurodegeneration [57,58]. This conclusion was based on evidence that decreasing lipid droplets via the overexpression of Bmm/ATGL leads to less neurodegeneration.…”
Section: A General Strategy For Distinguishing Between Different Lipisupporting
confidence: 70%
“…ADAM17 is increased in aging in mice and contributes to vascular remodeling and impaired endothelial wall shear stress mechanosensing [ 100 ]. Interestingly, in Drosophila , ADAM17 showed a protective role in neuronal and glial degeneration in the aging retina [ 101 ].…”
Section: The Role Of Aging On Bbb Function and Expression Of Sars-cov...mentioning
confidence: 99%
“…Dysregulated expression of ADAMs was reported in the RPE-choroid complex of AMD patients (16). In addition, the latest study showed that loss of ADAM17, one of intensively studied ADAM members, promotes AMD-like phenotypes (17).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Although genetic and environmental factors have been associated with the development of AMD, the etiology and pathogenesis of AMD remain largely unknown. Recently, dysfunctional MMPs have been reported to be associated with AMD in human beings ( 15 , 16 , 17 ). Genome-wide association studies showed that variations on tissue inhibitor of metalloproteinase 3 (TIMP3) are associated with the onset of AMD ( 15 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation